Banking, finance & monetary policy in Singapore - Luckett, Dudley G.; Schulzem, David L.M; Wong, Raymond W.Y (McGraw Hill, 1994)
Written for both students and professionals who don't have a background in finance or who aren't familiar with the financial sector of the Singapore economy, this text helps to transfer the standard ideas of money and banking intended for developed economies to the economy of Singapore.